Exploring the Psychosocial Dynamics of Pornography Consumption among Young Adult Women - Izaura Evanthe Salim; Fitrania Maghfiroh; Erriza Farizan Adani (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2026)
Pornography consumption among women has received limited attention in psychological research, as most studies primarily focus on men while female sexuality often remains socially sensitive. This study explores the psychosocial dynamics of pornography consumption among young adult women. A qualitative approach using thematic analysis was employed. Five women aged 18–25 years participated in semi-structured in-depth interviews. The findings indicate that pornography use commonly began with curiosity or accidental exposure through digital media and gradually developed into habitual behavior. For several participants, pornography functioned as a coping strategy to regulate negative emotions such as stress, loneliness, and emotional distress. Participants also reported various psychological and relational impacts, including guilt, intrusive thoughts, reduced concentration, and conflicts with personal moral and religious values. Social and cultural expectations toward women further intensified feelings of shame and negative self-evaluation. Beyond addictive behavioral patterns, the study also identified recovery processes involving emotional reflection and identity reconstruction. These findings highlight that pornography use among young adult women reflects complex psychosocial processes shaped by emotional needs, gender norms, and sociocultural contexts, emphasizing the importance of gender-sensitive psychological services and digital sexual education.